The Match Heart Rate and Running Profile of Elite Under-21 Hurlers During Competitive Match-Play; Journal of Strength and Conditioning Research; Vol. 32, iss. 10 - Young D. Damien; Mourot L. Laurent; Beato M. Marco; Coratella G. Giuseppe (2018, 2018)
Title screen